Gender Analisis And Planning in Rural Extension - Asmara, Nefi Aris Ambar (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2004)
Because women are positioned within their societies through a variety of different social relation (for example class ethnicity and ages as well as gender) the interests, they share as a gender category will be shaped in complex and often conficting ways. This statement will be examine in the implication for palning and implementation of development program for maximizing the beneficiaries-form Gender analysis perspective with the aimed at meeting the needs a rural women.